Influence of production process-induced surface topologies at varying roughness depths on the tribological properties of polyamide steel contact - Schubert, Dominik; Rohrmoser, Andreas; Herzog, Christoph; Wolf, Michael; Hagenah, Hinnerk; Merklein, Marion; Drummer, Dietmar (Journal of Polymer Engineering, 2023)
Friction and wear in a tribological system are directly dependent on the surface structure and roughness of the friction partners involved. In this article, a clear interaction between surface topologies and their roughness depth was identified for the material pairing polyamide 66 - steel. The typical correlation between roughness and wear, initially decreasing and increasing after a wear minimizing roughness, was found for all surface topologies, albeit at different levels. The effect of the surface topology is negligible at low roughness (S z < 2.0 μm) with adhesive wear processes determining the wear behaviour. At higher roughness depths (S z > 2.0 μm), the ability of the surface topology to form a stable transfer film determines the tribological behaviour by limiting the effect of abrasive wear processes. A stable transfer film is formed with sufficient roughness and undercuts in the direction of motion, which can be characterised by the average roughness depth, R z , in the direction of motion. Based on these empirical results, an explanatory model for the observed behaviour is presented.
Created from Fastlane, Scopus look-up
Keywords: polymer metal contact; surface structure; transfer film; tribology; wear

Influence of the injection molding process on the tooth deflection of plastic gears during operation - Herzog, Christoph; Drummer, Dietmar (VDI Verlag GMBH, 2023)
A new test methodology for in situ deformation and wear measurement of plastic gears has been developed at the Institute of Polymer Technology (LKT). The in situ gear test rig evaluates the time differences between successive index pulses from encoders on the input and output shafts. This measuring principle enables continuous measurement of elastic tooth deformation and the combination of plastic tooth deformation and flank wear by alternating between a high loading torque and a lower measuring torque. The newly developed measurement principle was used to investigate the influence of manufacturing-related geometrical and morphological deviations on elastic tooth deflection. The results show that an increased degree of crystallinity is associated with lower tooth deflections. Tool-related shape deviations, on the other hand, barely influence the deformation behavior. The design of the shaft-hub connection of the plastic gear, however, significantly influences the measured angular displacement between input and output shaft.
CRIS-Team Scopus Importer:2024-12-16

Influence of the injection molding process on the tooth deflection of plastic gears during operation - Herzog, Christoph; Drummer, Dietmar (5th International Conference on High Performance Plastic Gears 2023, 2023)
A new test methodology for in situ deformation and wear measurement of plastic gears has been developed at the Institute of Polymer Technology (LKT). The in situ gear test rig evaluates the time differences between successive index pulses from encoders on the input and output shafts. This measuring principle enables continuous measurement of elastic tooth deformation and the combination of plastic tooth deformation and flank wear by alternating between a high loading torque and a lower measuring torque. The newly developed measurement principle was used to investigate the influence of manufacturing-related geometrical and morphological deviations on elastic tooth deflection. The results show that an increased degree of crystallinity is associated with lower tooth deflections. Tool-related shape deviations, on the other hand, barely influence the deformation behavior. The design of the shaft-hub connection of the plastic gear, however, significantly influences the measured angular displacement between input and output shaft.
CRIS-Team Scopus Importer:2024-12-16

In situ investigation of the influence of varying load conditions on tooth deformation and wear of polymer gears - Herzog, Christoph; Wolf, Michael; Schubert, Dominik; Drummer, Dietmar (Forschung Im Ingenieurwesen-Engineering Research, 2022)
A new method for in situ deformation and wear measurement of polymer gears has been developed at the LKT and validated for polyamide-66 (PA66) gears at constant loading torque and rotational speed. This contribution contains a more comprehensive validation of the newly developed test method by examining polybutylenterephtalate (PBT) gears under varying loading conditions. The deformation test method is based on measuring and analysing the timing differences between the index pulse signals of rotary encoders on the input and output shaft of the test rig. Since the total tooth deformation is a combination of different effects, such as elastic and plastic deformation, thermal expansion and wear, different testing modes with a low and a high torque level are implemented to separate the effects of elastic deformation on the one hand and plastic deformation and wear on the other hand. As a consequence, the new test rig design allows a deeper understanding of the wear and deformation behaviour of polymer steel gear sets over time. This potential is used to analyse the interactions of different loading conditions on the time-dependent deformation of plastic gears. The influence of both, different transmitting torques and rotational speeds is examined. The test method shows good correlation with well-established ex situ measurements for different combinations of rotational speeds and loading torques and thus could be validated. Long-term gear tests under varying rotational speeds and loading torques show increasing wear and deformation at higher speeds and torques confirming the state of the art described in the literature. In addition, the time dependent deformation behaviour at different load conditions due to superposition of wear and plastic deformation could be analysed in detail.
Created from Fastlane, WoS look-up

In Situ Measured Tooth Flank Wear of Plastic Gears under Spectrum Loading - Herzog, Christoph; Wolf, Michael; Drummer, Dietmar (Polymers, 2022)
The wear behaviour of PBT-steel gear sets under temporarily changed load has been investigated using an in situ gear test rig developed at the LKT. The in situ test method is based on analysing the timing differences between the index pulses of rotary encoders on the input and output shaft of the test rig. The loading torque was varied between two levels and compared to the permanently applied equivalent average load in terms of the resulting tooth flank wear. Moreover, the number of load changes has been varied to analyse the influence of load changes on the gear wear. The results show that the applied load spectrum determines the resulting tooth flank wear even if the average applied load is the same. Moreover, it could be shown that the sequence of the applied load, i.e., the load history, plays an important role, since the applied load and the duration of the applied load within the run-in-stage disproportionately affect the wear behaviour over time.<br
Keywords: in situ; gear testing; plastic gears; gear wear; gear design

In Situ Test Rig for the Measurement of the Operating Characteristics of Polymer Gears - Schubert, Dominik; Herzog, Christoph; Drummer, Dietmar (Zeitschrift Kunststofftechnik, 2022)
In diesem Beitrag wird eine neue Methode zur in situ-Verformungs- und Verschleißmessung von Polymerzahnrädern unter Betriebslast vorgestellt. Dieser Ansatz basiert auf der hochgenauen Messung und Verfolgung von Zeitdifferenzen in den Indeximpulsen von Encodern auf der An- und Abtriebsseite eines Zahnradprüfstandes.<br

Limitations of the Check Calculation for Tooth Deformation of Plastic Gears According to Gear Design Guideline VDI 2736 - Herzog, Christoph; Drummer, Dietmar (Polymers, 2023)

Test Rig for The In Situ Measurement of The Elastic Tooth Deflection of Plastic Gears - Herzog, Christoph; Drummer, Dietmar (Polymers, 2023)